Analysis of Prognostic Factors for Resected Synchronous and Metachronous Liver Metastases from Colorectal Cancer. (11th July 2018) - Bartolini, Ilenia; Ringressi, Maria Novella; Melli, Filippo; Risaliti, Matteo; Brugia, Marco; Mini, Enrico; Batignani, Giacomo; Bechi, Paolo; Boni, Luca; Taddei, Antonio
Abstract : Background . Surgical treatment is the cornerstone in the management of colorectal cancer (CRC) liver metastases. The aim of this study is to identify clinicopathological factors affecting disease-free (DFS) and overall survival (OS) in patients undergoing potentially curative liver resection for CRC metastasis. Methods . All consecutive patients undergoing liver resection for first recurrence of CRC from February 2006 to February 2018 were included. Prognostic impact of factors related to the patient, primary and metastatic tumors, was retrospectively tested through univariate and multivariate analyses. Results . Seventy patients were included in the study. Median postoperative follow-up was 37 months (range 1–119). Median DFS and OS were 15.2 and 62.7 months, and 5-year DFS and OS rates were 16% and 53%. In univariate analysis, timing of metastasis presentation/treatment (combined colorectal and liver resection, "bowel first" approach or metachronous presentation) (p < 0.0001 ), ASA score (p = 0.003 ), chemotherapy after liver surgery (p = 0.028 ), T stage (p = 0.021 ), number of resected liver lesions (p < 0.0001 ), and liver margin status (p = 0.032 ) was significantly associated with DFS while peritoneal resection at colorectal surgery (p = 0.026 ), ASA score (p = 0.036 ), extension of liver resection (p = 0.024 ), chemotherapy after liver surgery (p = 0.047 ), and positive nodes (p = 0.018 ) with OS. In multivariate analysis, timing of metastasis presentation/treatment, ASA score, and chemotherapy (before and after liver surgery) resulted significantly associated with DFS and timing of metastasis presentation/treatment, positive nodes, peritoneal resection at colorectal surgery, and surgical approach (open or minimally invasive) of colorectal resection with OS. Conclusions. Surgery may provide good DFS and OS rates for CRC liver metastasis. Patient selection for surgery and correct timing of intervention within a multidisciplinary approach may be improved by taking into account negative prognostic factors which stress the importance of systemic therapy.